Anomalous vascular perforator of the internal thoracic artery supplying a pedicled transverse rectus abdominis myocutaneous flap—a case report. Issue 5 (23rd May 2022) - Neblett, Carlos; Logan, Leighton; Appiah, Kenneth; Knight, Kadeem
Abstract: The pedicled transverse rectus abdominis myocutaneous (TRAM) flap is an infrequently performed procedure relative to the more current microsurgical free tissue transfers in most centres around the world. However, in resource-limited centres where procedures requiring microsurgical intervention are rarely employed, the pedicled TRAM whose vascular axis is that of the superior epigastric artery, is an invaluable tool in the plastic surgeon's armamentarium both for breast reconstruction and chest wall soft tissue resurfacing. This a report of a case of variable anatomical vascular perforating branch of the internal thoracic artery, which was encountered while using a TRAM to resurface a chest wall defect after mastectomy was performed for locally advanced breast cancer.